Analysis of temperature sensor in all-pass microring resonator - Mohamad, Azam; Bahadoran, Mahdi; Daud, Suzairi; Chaudhary, Kashif Tufail; Aziz, M. S.; Jalil, M. A.; Ali, Jalil; Yupapin, P. P. (My University, 2016)
The temperature sensor using all-pass microrin resonator (APMRR) investigated theoretically and analyzed. An optical bright soliton is used as a probe to study the effect of applied temperature on the light behavior pass through microring waveguide. The split-step Fourier method is used to study the pulse propagation inside the APMRR. Result shows that the rise of temperature on peak amplitude ratio fit with quadratic line in temperature range of 27 oC-37 oC. . The temperature at 30 oC generate higher slope of reduction compare to temperature at 36oC. The amplitude ratio is reduced into 0.6 (-4.4370 dB) when the temperature increased as small as 1 oC. The operating range for all-pass resonator is 97 oC with amplitude reduction of -8.3975 dB.
Keywords: Ring resonator; SOI waveguide; Split-Step Fourier method; Temperature sensing